LINGUISTIC AND LINGUODIDACTIC FOUNDATIONS OF INTERPRETING ETHNOCULTURAL UNITS IN AI-BASED DICTIONARIES (International journal of artificial intelligence, 2026)
This article analyzes the linguistic and linguodidactic foundations of interpreting ethnocultural units in AI-based dictionaries. It identifies the main problems in the representation of culture-specific lexical units in digital lexicographic systems and substantiates the necessity of a multidimensional, culturally oriented model of explanation. The study shows that simplified and universalized definitions do not ensure an adequate understanding of ethnocultural semantics and proposes a set of principles for improving lexicographic description, including cultural markedness preservation, multilevel interpretation and adaptive presentation for different user groups. It is argued that the integration of linguistic, cultural and pedagogical components in AI-based dictionaries significantly increases their educational and intercultural value.